India incorporated - Vittal, N. (New Delhi, 1995)
The new economic policy of the Government and the need for strategic thinking on the role of India in a competitive world are inter-linked. The articles in this book highlight those specific sectors electronics and telecommunications-which are vital in the age of information technology. The author, an eminent and senior member of the Indian Administrative Service, has been closely associated with some of the strategic and technology intensive Departments, namely, Atomic Energy, Electronics and Telecommunications and brings to bear upon his writings and speeches, the valuable experience in these spheres. The basic thrust of articles is to look at the lessons that we can learn from a country like Japan which has emerged as Japan Incorporated. Can India be India Incorporated? The book provides stimulating perceptions.
Keywords: Electronic industries-India